Pain in Hidradenitis Suppurativa: A Cross-sectional Study of 1,795 Patients - Piotr K. Krajewski; Łukasz Matusiak; Esther von Stebut; Michael Schultheis; Uwe Kirschner; Georgios Nikolakis; Jacek C. Szepietowski (Medical Journals Sweden, 2021)
Hidradenitis suppurativa is a chronic, inflammatory skin disorder that affects the pilosebaceous unit of the intertriginous body areas. Pain is one of the most important problems in patients with hidradenitis suppurativa. The aim of this study, which included 1,795 patients, was to evaluate the prevalence and characteristics of pain. The intensity of pain was assessed with a numerical rating scale. In addition, pain intensity was correlated with various clinical features. Pain was reported by 83.6% of subjects. The majority of patients (77.6%) experienced mild pain; women and smokers tended to experience more intense pain. Pain intensity was greater in patients with multiple affected skin areas and correlated positively with the number of those affected areas (r = 0.151, p < 0.001). There was no difference in pain intensity between affected locations. The worst pain was observed in the patients with the most severe disease and it would weaken significantly along with the severity of hidradenitis suppurativa (assessed using the Hurley staging system and the International Hidradenitis Suppurativa Severity Score System).